FIQIH INDONESIA MENURUT PEMIKIRAN HASBI ASH-SHIDDIQI, HAZAIRIN DAN MUNAWIR SYADZALI - Ma'arif, Toha (Universitas Islam Negeri Raden Intan Lampung, 2015)
Ash-Shiddieqy’s introduction of term Indonesian fiqhwas a compromise between Indonesian nationalismand Muslim reformism. By turning Indonesiancustoms into one of the sources of Indonesian fiqh.His conceptualization of an ‘Indonesian fiqh’, throughhis immersion in both classical Arabic texts and thewritings of later reformists from the Middle East, andHazairin’s stress on the role of particular culturalcircumstances in shaping the Islamic content ofIndonesian law, both foreshadowed comparableinitiatives in the 1980s and 1990s, such as MunawirSjadzali’s Reaktualisasi Agenda. All theses initiativescontinue to form the background of discussions anddebates on law among Indonesian Muslim intellectualsat the beginning of the twenty-first century.